Thioredoxin-1 promotes colorectal cancer invasion and metastasis through crosstalk with S100P. (10th August 2017) - Lin, Feiyan; Zhang, Peili; Zuo, Zhigui; Wang, Fule; Bi, Ruichun; Shang, Wenjing; Wu, Aihua; Ye, Ju; Li, Shaotang; Sun, Xuecheng; Wu, Jianbo; Jiang, Lei
Abstract: Thioredoxin-1 (Trx-1) is a small redox-regulating protein, which plays an important role in several cellular functions. Despite recent advances in understanding the biology of Trx-1, the role of Trx-1 and its underlying signaling mechanism in colorectal cancer (CRC) metastasis have not been extensively studied. In this study, we observed that Trx-1 expression is increased in CRC tissues compared to the paired non-cancerous tissues and is significantly correlated with clinical staging, lymph node metastasis and poor survival. Overexpression of Trx-1 enhanced CRC cell invasion and metastasis in vitro and in vivo . Conversely, suppression of Trx-1 expression decreased cell invasion and metastasis in vitro and in vivo . Moreover, Trx-1 activates S100P gene transcription. S100P, in turn, promotes Trx-1 expression and nuclear localization by upregulating p-ERK1/2 and downregulating TXNIP expression. Our finding provides new insight into the mechanism of Trx-1/S100P axis in the promotion of CRC metastasis, and suggests that the Trx-1/S100P axis and their related signaling pathways could be novel targets for the treatment of metastatic CRC. Highlights: Trx-1 expression is associated with poor prognosis in CRC patients. Overexpression of Trx-1 enhances CRC invasion and metastasis in vitro and in vivo . Trx-1 knockdown inhibits CRC invasion and metastasis in vitro and in vivo . Trx-1 activates S100P gene transcription. S100P promotes Trx-1 expression and nuclear localization by upregulating p-ERK1/2 and downregulating TXNIP expression.